Profil Kemampuan Memecahkan Masalah Peserta Didik MA Darul Muqorrobin pada Pembelajaran Biologi - Dewi Arum Budianti; Fenny Roshayanti; Muhammad Syaipul Hayat; Muhammad Azmi Syafiq (Perkumpulan Kualitama Edukatika Indonesia, 2022)
This study aims to describe the problem-solving ability profile of students in biology learning at MA Darul Muqorrobin. This research is descriptive qualitative with the technique of collecting data which is netted with a problem-solving ability test in biology learning. The subject in this study is students of class X MA Darul Muqorrobin for the academic year 2021/2022, totaling 53 people. Generally, the problem solving ability of students in biology learning at MA Darul Muqorrobin is in poor criteria where the indicators of understanding the problem are 51% (not good), designing problem solving 32% (not good), implementing problem solving 38% (not good) and recheck the troubleshooting result of 37% (not good). To improve problem-solving skills in biology learning, teachers need to apply problem-based learning models and media and create a learning environment that supports problem-solving methods that can increase students' learning activities, motivation and cognitive abilities.